Pelatihan Kepedulian Keselamatan Dan Keamanan Serta Pelayanan Angkutan Udara Pada Era Digitalisasi Penerbangan Kepada Mahasiswa/I Dan Dosen Politeknik Siber Dan Sandi Negara - Agoes Soebagio; Elfi Amir; Dwi Afriyanto; Ika Endrawijaya; Wahyudono Wahyudono; Sundoro Sundoro; M. Chandra Kusumah (Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of the digitalization era has brought significant impacts across various sectors, including the air transportation sector. Aviation safety, security, and service quality are no longer dependent solely on operational aspects but also on the increasingly advanced use of digital technologies. However, the understanding of aviation safety, security, and service standards remains limited within non-aviation higher education environments, particularly at the Polytechnic of Cyber and Crypto Technology (Politeknik Siber dan Sandi Negara), which has primarily focused on cyber technology and cryptography. In response to this issue, a Community Service team consisting of one lead proposer and five lecturer members conducted a Training on Safety and Security Awareness and Air Transport Services in the Era of Aviation Digitalization at the Polytechnic of Cyber and Crypto Technology on June 25, 2025. The activity was attended by 481 participants comprising students, lecturers, and academic staff. The training was delivered through public lectures, interactive discussions, and simulations to provide comprehensive insights into the importance of aviation safety and security in the digital era, while also fostering cross-disciplinary collaboration between the Polytechnic of Cyber and Crypto Technology and the Indonesian Aviation Polytechnic of Curug. Based on the evaluation results, participants demonstrated improved knowledge and awareness regarding aviation safety, security, and air transport services. Moreover, the program succeeded in raising awareness of the importance of integrating digital security and aviation operations as an essential effort to address the challenges of modern air transportation.